Experimental and numerical investigations on the slate shearing mechanical behavior - Gu, Jinze (2025)
Multi-scale assessment of shear behavior in the tunnel carbonaceous slate is critical for evaluating the stability of the surrounding rock. In this study, direct shear tests were conducted on carbonaceous slates from the Muzhailing Tunnel, considering five bedding dip angles (β) and four normal stresses (σn). The micro-mechanism was also examined by combining acoustic emission (AE) and energy rate with PFC2D Version 5.0 (particle flow code 2D Version 5.0 software) numerical simulations. The results showed a linear relationship between peak shear stress and normal stress, with the rate of increase inversely related to β. Cohesion increased linearly with β, while internal friction angle and AE activity decreased; the energy release rate is 3.92 × 108 aJ/s at 0° and 1.93 × 108 aJ/s at 90°. Shearing along the preset fracture plane was the main failure mode. Increased normal stress led to lateral cracks perpendicular to or intersecting the shear plane. Cracks along the bedding plane formed a broad shear band with concentrated compressive force, and inclined bedding was accompanied by a dense tension chain along the bedding plane.